The relationship between knowledge management pratices and non-academic staff performance in Universiti Teknologi MARA Cawangan Kelantan / Nur Shahiera Ayunie Binti Muhd Hafiz - Muhd Hafiz, Nur Shahiera Ayunie (2017)
The purpose of this study was to investigate the relationship between knowledge management practices and non-academic staff performance in Universiti Teknologi MARA Cawangan Kelantan. The sample for the study is consisted of 144 out of 230 non-academic staffs. The Pearson correlation coefficient and Independent t-test in the Statistical Package for Social Sciences (SPSS) version 22 were utilized for the analysis of data. The finding revealed a significant and positive relationship between knowledge management practices and non academic staff performance. Specifically, knowledge acquisition, knowledge dissemination and knowledge utilization were revealed to have a significant and positive relationship that influence on staff performance. Based on this finding, it was concluded that knowledge dissemination was most applied by the staffs. It is recommended that the staffs need to give feedback and communicate each other to strengthen their knowledge management practices especially knowledge acquisition, knowledge dissemination and knowledge utilization in their everyday activities in Universiti Teknologi MARA Cawangan Kelantan.